Best Answer

4x+5=6x-7

To solve this, us the 5 steps for solving an equation:

1. Eliminate parentheses/Distribute Not applicable. No parentheses or need to distribute.

2. Add like terms. Not applicable. No like terms.

3. Eliminate the variable on one side or the other. 4x+5=6x-7

Reverse the sign of 4x, making it -4x and put it in on the left side and the right side. This makes it:

4x-4x+5=6x-7-4x

Now add like terms

5=2x-7

4. Eliminate the constant term on the side of the variable. 5=2x-7

Reverse the constant term on the side of the variable (-7 becomes +7) and put one on each side:

5+7=2x-7+7

Now add like terms:

12=2x

5. Solve for the variable by dividing both sides by the coefficient 12=2x

This rule means that whatever the number is before x (in this case, 2), divide the other side by it.

12 divided by 2=2x divided by 2

And solve

6=x

Q: 4x plus 5 equals 6x -7?

Write your answer...

Submit

Still have questions?

Continue Learning about Calculus

x=5. 10x-4x (6x) +10-6x (=10) If 10 is 2x, x=5.

2x + 5 = 7 - 4x ie 2x + 4x = 7 - 5 ie 6x = 2 x = one third.

8x2 + 15 + 26x = 8x2 + 26x + 15 = 8x2 + 20x + 6x + 15 = 4x(2x + 5) + 3(2x + 5) = (2x + 5)(4x + 3)

3x+5= 4x-10+10 +103x+15= 4x-3x -3x15=X

If: 4x = x+15 Then: x = 5

Related questions

4x-15=6x-4x 4x-22.4=2x 2x=22.4 x=11.2

6x + 3 = 2x + 5 4x = 2 x=1/2

-6x + 5 = -4x + 19add 6x to both sides5 = 2x + 19subtract 19 from both sides-14 = 2xdivide both sides by 2-7 = x

x=5. 10x-4x (6x) +10-6x (=10) If 10 is 2x, x=5.

6x - 12 + 4x + 5 = 06x + 4x = 12 - 510x = 7x = 7/10

4x - 5 + 2x = 376x - 5 = 376x = 37 + 56x = 42x = 42 / 6x = 7

Multiply the first by 3 and the second by -2

2x + 5 = 7 - 4x ie 2x + 4x = 7 - 5 ie 6x = 2 x = one third.

6x + 8 = 6 6x = -2 x = -2/6 x = -1/3

10x-7=4x+5 +7 +7 10x=4x+12 -4x -4x 6x=12 /6 /6 x=2

If: 1-2x-5 = 4x+2 Then: -2x-4x = 2-1+5 And: -6x = 6 So: x = -1

6x + 5